Manifestaciones bucales en pacientes bajo tratamiento antihipertensivo. centro de salud Nro. 1 Tulcán - Estrada Castro, Silvana Ginnelle (2021)
ABSTRACT The work presented considers that antihypertensive drugs alter the metabolism of cells, creating changes in the organism's pre-existing functions. Therefore, this research's objective was to determine the possible relationship between taking antihypertensive drugs and oral manifestations that they cause. The research was descriptive, qualitative-quantitative, cross-sectional, correlational, and non-experimental with a population of 127 records of clinical information, including data collection sheets and information from medical records, hypertensive patients belonging to the Health Center No. 1 in the city of Tulcán, these data were subjected to selection criteria obtaining a sample of 106 records. The results found showed that the different groups of antihypertensive drugs generate metabolic changes in the organism with the presence of different oral manifestations such as Xerostomy in 75.5%, Taste alterations in 54.7%, Gingival hyperplasia in 36.8%, Aphthous ulcers in 14.2%, Erythema multiforme in 7.5%, Lichenoid reactions in 5.7%, Bullous pemphigoid in 1.9%, Angioneurotic edema in 0.9%. Finally, it was established a significant relationship between antihypertensive drugs consumption and Xerostomy (p=0.00), Taste alterations (p=0.00), and Gingival hyperplasia (p=0.014). Keywords: arterial hypertension, antihypertensive drugs, oral pathological manifestations. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258